2020
DOI: 10.3390/cancers13010047
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Glioblastoma: From Molecular Landscape to New Treatment Perspectives

Abstract: Glioblastoma is the most frequent and aggressive form among malignant central nervous system primary tumors in adults. Standard treatment for newly diagnosed glioblastoma consists in maximal safe resection, if feasible, followed by radiochemotherapy and adjuvant chemotherapy with temozolomide; despite this multimodal treatment, virtually all glioblastomas relapse. Once tumors progress after first-line therapy, treatment options are limited and management of recurrent glioblastoma remains challenging. Loco-regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
126
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(135 citation statements)
references
References 198 publications
(288 reference statements)
4
126
0
5
Order By: Relevance
“…Yet, the randomized phase 2 REGOMA trial [ 7 ] showed a statistically longer OS in recurrent GBM patients when treated with regorafenib compared to standard lomustine: the 12m-OS rate was 38.9% versus 15.0%, respectively. Due to this important clinical benefit, regorafenib was included in the NCCN 2020 guidelines and was approved by the Italian Medicines Agency (AIFA) as the preferred treatment for the recurrent GBM population [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, the randomized phase 2 REGOMA trial [ 7 ] showed a statistically longer OS in recurrent GBM patients when treated with regorafenib compared to standard lomustine: the 12m-OS rate was 38.9% versus 15.0%, respectively. Due to this important clinical benefit, regorafenib was included in the NCCN 2020 guidelines and was approved by the Italian Medicines Agency (AIFA) as the preferred treatment for the recurrent GBM population [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…While chemoradiotherapy with temozolomide (TMZ) represents standard first-line therapy after surgery [ 1 ], the standard of care for second-line treatment has not been defined. Treatment options include re-surgery, re-irradiation and systemic pharmacotherapy—mostly nitrosoureas [ 2 , 3 ]. Bevacizumab demonstrated that it prolongs progression-free survival (PFS) without improving overall survival (OS) [ 4 ]; yet, immunotherapy with checkpoint inhibitors showed no efficacy in glioma patients [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the complete resection of GBM has been challenging due to the invasive growth pattern and the functional area involvement. It has been almost inevitable that the tumor-infiltrating parenchyma tissue eventually relapsed even after surgical resection (8,9). The resistance to chemotherapy drug temozolomide (TMZ) was mainly caused by O6-methylguanine-DNA methyltransferase over-expression, mismatch repair and base excision repair (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…However, the intrinsic characteristics of GBM cells, which include rapid growth and infiltration into the normal brain tissues, hinder the successive removal of the primary lesion; it frequently leads to postoperative recurrence despite the advances in intraoperative imaging techniques that facilitate intraoperative analysis of tumor and normal brain tissues [ 3 , 4 ]. In addition, the emergence of chemo resistance, especially to temozolomide (TMZ), which is the most effective drug for GBM at present, further contributes to tumor recurrence, resulting in poor clinical outcomes [ 5 ]. Therefore, it is urgent to develop a new and effective drug for GBM based on a molecular mechanism that is different from that of TMZ.…”
Section: Introductionmentioning
confidence: 99%